Tourism Development Towards International Competitive Tourism in Promoting The Economy of East Java - Yustie, Renta; Ariska, Ricky Angga; Purwitasari, Fadilla (Journal of Developing Economies, 2022)
The tourism sector is one of the economic sectors that has a characteristic and contributes to the GRDP (Gross Regional Domestic Product) in East Java. East Java has a large tourism potential with a pattern of tourism development that can contribute to increasing East Java's economic growth. The role of the tourism sector in East Java can improve the national economy and contribute to the national GDP (Gross Domestic Product) of Indonesia. This study aims to determine the development of the tourism sector in East Java during 2016 to 2020 using the LQ (Location Quotient) method so as to produce the tourism sector in the basic or non-basic sector category. The data used is secondary data and this research is a quantitative research. The results of the calculation of LQ (Location Quotient) can help develop and build the tourism sector that is in the basic or non-basic category. Keywords: LQ, GDP, Tourism Sector, Development Economic, East Java